Substantiating the effectiveness of projects for the construction of dual systems of fire suppression - Ratushnyi, Roman; Khmel, Piotr; Tryhuba, Anatoliy; Martyn, Evgen; Prydatko, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2019)
The expediency of the systemic activity of cross-border operational rescue units due to the creation of dual systems of cross-border fire suppression was substantiated. Dual fire suppression systems are temporarily created systems (for the period of liquidation of fires at the borders) from the resources of two neighboring countries in order to restrict the development and suppress fires, as well as to protect people and wealth from them. The objects of configuration of such systems are the number and composition of technical means for fire suppression, the number and speciality of firefighters-rescuers, as well as supplies for the liquidation of fires. The analysis of the relationships between the objects of configuration of dual systems of cross-border firefighting was performed and the feasibility of developing the toolsets to determine the effectiveness of the projects the dual system creation was substantiated. Three variants for determining the effectiveness of the projects of creating dual systems of cross-border fire-suppression were proposed. They are the basis for the developed geometric model of substantiation of the configuration of the projects of creation of dual systems of cross-border fire suppression. It was found that the range of a change of the parameters of firefighting-rescue units of two states varies from 0 to 1, which affects the effectiveness of the projects of creation of dual systems of cross-border fire-suppression. The absence of the extremum of dependence of effectiveness of the projects of creating dual systems of cross-border fire-suppression on the number of forces and facilities of two neighboring states was found. The dependence of the maximum value of effectiveness of the projects of create of dual systems of cross-border fire suppression on its parameters indicates the need for taking into account the characteristics of the changing project environment, as well as organizational components of these projects. According to the results of geometric modeling, the mutual influence of five indicators on effectiveness of the projects of creation of dual systems of cross-border fire suppression was substantiated.